Water quality index of selected stations at Sungai Rasau, Ayer Hitam Forest Reserve, Selangor - Arippin, Mohd Aizat; Mohamad Kasim, Mohamad Roslan (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The effects of human activities and land development are often related with changes to stream water quality. A study was carried out at Sg. Rasau, Ayer Hitam Forest Reserve, to determine its water quality status. Eight sampling stations were chosen where weekly sampling over seven weeks was carried out. BOD, COD, pH, Ammoniacal Nitrogen, TSS and DO were analysed for the water quality status based on the Water Quality Index (WQI) of the Department of Environment, Malaysia. The WQI ranged between 73.64 to 96.81 which fell into Class II and Class III, respectively. For Class II, the water is suitable for recreational activity but requires water treatment for water supply. For Class III, extensive treatment is required for water supply although suitable for livestock.